2018
DOI: 10.1038/s41598-018-24500-1
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatitis Delta Virus accumulation requires paraspeckle components and affects NEAT1 level and PSP1 localization

Abstract: The Hepatitis Delta Virus (HDV) relies mainly on host proteins for its replication. We previously identified that PSF and p54nrb associate with the HDV RNA genome during viral replication. Together with PSP1, these proteins are part of paraspeckles, which are subnuclear bodies nucleated by the long non-coding RNA NEAT1. In this work, we established the requirement for PSF, p54nrb and PSP1 in HDV replication using RNAi-mediated knockdown in HEK-293 cells replicating the HDV RNA genome. We determined that HDV re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…Even though the function of NEAT1 is still not fully understood, several reports have suggested that increased NEAT1 expression regulates the expression of certain genes by sequestering specific mRNAs and proteins into paraspeckles (10 -12). NEAT1 expression is up-regulated in response to different cellular stresses, including viral infections, proteasome inhibition, oncogene-induced replication stress, and hypoxia (11)(12)(13)(14)(15)(16)(17). Emerging evidence suggests that NEAT1 plays a cytoprotective role, as cells deficient of NEAT1 display increased sensitivity toward stress-induced cell death (11,15).…”
mentioning
confidence: 99%
“…Even though the function of NEAT1 is still not fully understood, several reports have suggested that increased NEAT1 expression regulates the expression of certain genes by sequestering specific mRNAs and proteins into paraspeckles (10 -12). NEAT1 expression is up-regulated in response to different cellular stresses, including viral infections, proteasome inhibition, oncogene-induced replication stress, and hypoxia (11)(12)(13)(14)(15)(16)(17). Emerging evidence suggests that NEAT1 plays a cytoprotective role, as cells deficient of NEAT1 display increased sensitivity toward stress-induced cell death (11,15).…”
mentioning
confidence: 99%
“…HDV RNA is known to associate with the pre-mRNA splicing factors p54nrb and PSF, which are the two core protein components of the mammalian paraspeckles 30 . The knockdown of p54nrb, PSF, or PSP1 paraspeckle proteins reduces HDV RNA genome accumulation 31 . Recent evidence links components of mammalian SWI/SNF complexes, namely BRG1 and BRM, to paraspeckle assembly without requiring their ATPase activity 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Early analyses in mice indicated that whereas NEAT1_1 is ubiquitously expressed, the expression pattern of NEAT1_2, and thus the presence of paraspeckles, is more restricted 5 . Emerging evidence now suggests that NEAT1_2 and paraspeckles play critical roles in orchestrating specific gene expression upon cellular stress and at specific developmental stages [9][10][11][12][13][14][15][16][17][18] . Importantly, it was recently shown that the expression of NEAT1_2, but not total NEAT1, was associated with aggressive cancers 15 .…”
Section: Discussionmentioning
confidence: 99%